Development of a New Multifunctional Cationic Surfactant System with Corrosion Inhibiting Ability. (19th September 2017) - Yao, Erdong; Liang, Tianbo; Li, Yuan; Sun, Jiaxin; Zhou, Fujian
Abstract : Four alkyl propargyl bis(hydroxyethyl) ammonium surfactants with different lengths in hydrophobic tail (C8–C16) are prepared by direct alkylation of diethanolamine with alkyl bromides. The surfactants exhibit excellent surface properties. The critical micelle concentration (CMC) values of the surfactants 2c and 2d are found to be 7.63 × 10 - 4 and 1.23 × 10 - 4 mol/L, and the corresponding surface tension (γ C M C ) values are 31.83 and 31.69 mN/m, respectively. Furthermore, all of the synthesized propargyl quaternary ammonium salts are found to be very effective in inhibiting the corrosion of N80 steel (IE% = 92–98%). They can be used at a relatively high temperature (≥90°C) and a low concentration (0.039 wt.%). In addition, the apparent viscosity of surfactant 2d is studied at various temperatures, and it can be used as a viscoelastic surfactant up to 100°C. The synthesized surfactants possess multiple functions and have a very good compatibility with VES systems. They can be potentially used in various oil field applications such as enhanced oil recovery, fracturing, acid diversion, and well stimulation.